The Effect Of Giving Foot Massage To Lower Blood Pressure In Patients With Hypertension In The Family Context: Case report: Pengaruh Pemberian Foot Massage Untuk Menurunkan Tekanan Darah Pada Pasien Dengan Hipertensi Dalam Konteks Keluarga: Case Report - Amira Hijriani; Chairani, Reni (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Hypertension is an increase in systolic blood pressure ? 140 mmHg and diastolic blood pressure ? 90 mmHg, Mostly hypertension occurs without signs and symptoms, so patients do not realize they have been diagnosed with hypertension, that's why hypertension is known as the Silent Killer. South Jakarta ranks 3rd out of 6 regions in DKI Jakarta with a prevalence of hypertension based on doctor's diagnosis of 10.92%. Foot massage is one of complementary therapy that is safe and applicable that aims to lower blood pressure. The scientific work aims to apply foot massage to lower blood pressure in hypertensive patients. The method used is case study with a sample of 1 patient in 3 consecutive days for 30 minutes with 12 steps during 15 minutes in each foot. The results after giving foot massage there is a decrease in blood pressure from the first day to the third day, the average systolic pressure dropped by 6.4 mmHg and diastolic pressure dropped by 5mmHg. This shows the effectiveness of foot massage on lowering blood pressure. Through this study, foot massage is an alternative solution to efforts to reduce blood pressure non-pharmacologically. This study can be a reference and initial source of information for further research, in addition to further research is expected to look at other aspects such as anxiety levels and sleep patterns of patients.